Influence of configuration and anchor in ligamentous augmentation to prevent proximal junctional kyphosis: A finite element study - Liu, Wei; Zang, Lei; Kang, Nan; Yang, Lihui; An, Likun; Zhu, Wenyi; Hai, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Ligament augmentation has been applied during spinal surgery to prevent proximal junctional kyphosis (PJK), but the configuration and distal anchor strategies are diverse and inconsistent. The biomechanics of different ligament augmentation strategies are, therefore, unclear. We aimed to create a finite element model of the spine for segments T6–S1. Model Intact was the native form, and Model IF was instrumented with a pedicle screw from segments T10 to S1. The remaining models were based on Model IF, with ligament augmentation configurations as common (CM), chained (CH), common and chained (CHM); and distal anchors to the spinous process (SP), crosslink (CL), and pedicle screw (PS), creating SP-CH, PS-CHM, PS-CH, PS-CM, CL-CHM, CL-CH, and CL-CM models. The range of motion (ROM) and maximum stress on the intervertebral disc (IVD), PS, and interspinous and supraspinous ligaments (ISL/SSL) was measured. In the PS-CH model, the ROM for segments T9–T10 was 73% (of Model Intact). In the CL-CHM, CL-CH, CL-CM, PS-CM, and PS-CHM models, the ROM was 8%, 17%, 7%, 13%, and 30%, respectively. The PS-CH method had the highest maximum stress on IVD and ISL/SSL, at 80% and 72%, respectively. The crosslink was more preferable as the distal anchor. In the uppermost instrumented vertebrae (UIV)+1/UIV segment, the CM was the most effective configuration. The PS-CH model had the highest flexion load on the UIV+1/UIV segment and the CL-CM model provided the greatest reduction. The CL-CM model should be verified in a clinical trial. The influence of configuration and anchor in ligament augmentation is important for the choice of surgical strategy and improvement of technique.